2020
DOI: 10.1093/geronb/gbaa145
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness in Later Life and Reaching Longevity: Findings From the Longitudinal Aging Study Amsterdam

Abstract: Objectives There is an increasing research interest in factors that characterize those who reach exceptionally old ages. Although loneliness is often associated with an increased risk for premature mortality, its relationship with reaching longevity is still unclear. We aimed to quantify the association between (social/emotional) loneliness and the likelihood of reaching the age of 90 years in men and women separately. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Reaching 90 years of age was negatively correlated with social loneliness in a longitudinal study from Amsterdam on 64-90-year-old men and women (N=2,080) (Brandts et al, 2021). Greater morbidity and mortality have been associated with loneliness.…”
Section: Morbidity and Mortalitymentioning
confidence: 97%
“…Reaching 90 years of age was negatively correlated with social loneliness in a longitudinal study from Amsterdam on 64-90-year-old men and women (N=2,080) (Brandts et al, 2021). Greater morbidity and mortality have been associated with loneliness.…”
Section: Morbidity and Mortalitymentioning
confidence: 97%
“…A distinction can be made between emotional loneliness, the feeling of missing an intimate relationship, and social loneliness, the feeling of missing a wider social network (Weiss, 1973). The distinction was later confirmed by studies that have shown that social and emotional loneliness were only moderately correlated (Dahlberg & McKee, 2014), were present in latent class analyses (Hyland et al, 2018), and were differently associated with risk factors and a variety of physical and mental health outcomes (Brandts et al, 2020;Dahlberg & McKee, 2014;Diehl et al, 2018;Hyland et al, 2018;McHugh Power et al, 2018;Nieboer et al, 2020;OʼSúilleabháin et al, 2019;Peerenboom et al, 2015). Regarding risk factors, social loneliness has been associated with, e.g., low physical activity, immigrant background, and male gender (Dahlberg & McKee, 2014;Diehl et al, 2018), while emotional loneliness has been associated with, e.g., not being in a committed relationship, neuroticism and non-receipt of informal care (Dahlberg & McKee, 2014;Diehl et al, 2018;Nieboer et al, 2020;Peerenboom et al, 2015).…”
Section: Introductionmentioning
confidence: 96%
“…Emotional loneliness, but not social isolation or perceived social support, is associated with a greater risk of developing dementia [22], although perceived social support seems to protect against dementia in men [23]. Researchers have found social loneliness, but not the emotional facet, to be associated with longevity in women [24], whereas emotional loneliness is associated with an increased risk of all-cause mortality in older adults living alone [25]. Some evidence suggests that emotional loneliness, and not the perceived quantity of interpersonal connections, is more likely associated with the risk of depression and poor mental health (psychological distress) [26,27].…”
Section: Introductionmentioning
confidence: 99%